Fact and Fiction: The Contribution of Archives to the Study of Literary Translation - Wardle, Mary (Vertimo studijos, 2019)
This paper examines the role of traditional physical archives within Translation Studies research, investigating the contribution that such resources can add, providing information that otherwise would not be available in existing scholarly volumes, academic journals and digital material. The question is illustrated with the specific case of F. Scott Fitzgerald’s The Great Gatsby (1925) and its first two translations into Italian, carried out respectively in 1936 by Cesare Giardini and 1950 by Fernanda Pivano. Both translations were published by Mondadori, Italy’s largest publishing company, as part of two different series, I romanzi della palma and the later Medusa collection.Adopting a microhistory approach, the study of these translations, through the resource-rich archives of the Fondazione Arnoldo e Alberto Mondadori in Milan, can shed light on a number of issues that the text alone cannot provide: documentation, including the other books published in the same series, highlights the target audience that Mondadori were seeking to address; the paratextual elements of the books themselves are revealing of the prominence (or otherwise) of American literature in general and Fitzgerald in particular within the Italian literary polysystem at the time of their publication; in the case of the first translation, readers’ reports on the novel indicate how the censors of the Fascist regime might receive the somewhat racy themes contained in the book, while, in the case of the 1950 translation, correspondence between the publisher, literary agents and the translator herself highlight the many issues surrounding the ultimate publication of the volume.
Keywords: archives; The Great Gatsby; translation history; archival research